Impact of fecal occult blood on obscure gastrointestinal bleeding: Observational study - Kobayashi, Yuka (World J Gastroenterol, 2015)
AIM: To elucidate the association between small bowel diseases (SBDs) and positive fecal occult blood test (FOBT) in patients with obscure gastrointestinal bleeding (OGIB). METHODS: Between February 2008 and August 2013, 202 patients with OGIB who performed both capsule endoscopy (CE) and FOBT were enrolled (mean age; 63.6 ± 14.0 years, 118 males, 96 previous overt bleeding, 106 with occult bleeding). All patients underwent immunochemical FOBTs twice prior to CE. Three experienced endoscopists independently reviewed CE videos. All reviews and consensus meeting were conducted without any information on FOBT results. The prevalence of SBDs was compared between patients with positive and negative FOBT. RESULTS: CE revealed SBDs in 72 patients (36%). FOBT was positive in 100 patients (50%) and negative in 102 (50%). The prevalence of SBDs was significantly higher in patients with positive FOBT than those with negative FOBT (46% vs 25%, P = 0.002). In particular, among patients with occult OGIB, the prevalence of SBDs was higher in positive FOBT group than negative FOBT group (45% vs 18%, P = 0.002). On the other hand, among patients with previous overt OGIB, there was no significant difference in the prevalence of SBDs between positive and negative FOBT group (47% vs 33%, P = 0.18). In disease specific analysis among patients with occult OGIB, the prevalence of ulcer and tumor were higher in positive FOBT group than negative FOBT group. In multivariate analysis, only positive FOBT was a predictive factors of SBDs in patients with OGIB (OR = 2.5, 95%CI: 1.4-4.6, P = 0.003). Furthermore, the trend was evident among patients with occult OGIB who underwent FOBT on the same day or a day before CE. The prevalence of SBDs in positive vs negative FOBT group were 54% vs 13% in patients with occult OGIB who underwent FOBT on the same day or the day before CE (P = 0.001), while there was no significant difference between positive and negative FOBT group in those who underwent FOBT two or more days before CE (43% vs 25%, P = 0.20). CONCLUSION: The present study suggests that positive FOBT may be useful for predicting SBDs in patients with occult OGIB. Positive FOBT indicates higher likelihood of ulcers or tumors in patients with occult OGIB. Undergoing CE within a day after FOBT achieved a higher diagnostic yield for patients with occult OGIB.